Dream teams : working together without falling apart - Snow, Shane (Portfolio/Penguin, an imprint of Penguin Random House LLC, 2018)
"Award-winning entrepreneur and journalist Shane Snow reveals the counterintuitive reasons why so many partnerships and groups break down--and why some break through. The best teams are more than the sum of their parts, but why does collaboration so often fail to fulfill this promise? In Dream Teams, Snow takes us on an adventure through history, neuroscience, psychology, and business, exploring what separates groups that simply get by together from those that get better together." -- Amazon.com.